Macrocycle‐Based Hydroxamate Ligands for Complexation and Immunoconjugation of 89Zirconium for Positron Emission Tomography (PET) Imaging. Issue 3 (25th January 2016) - Boros, Eszter; Holland, Jason P.; Kenton, Nathaniel; Rotile, Nicholas; Caravan, Peter
Abstract: Four novel chelators (L1 –L4 ) and their 89 zirconium complexes were prepared and compared with the 89 zirconium desferrioxamine B (DFO) complex. The new chelates are based on 1, 4, 7, 10‐tetraazacyclododecane (cyclen) and 1, 4, 8, 11‐tetraazacyclotetradecane (cyclam) scaffolds and present either three or four hydroxamate arms for coordination with Zr 4+ ions with coordination numbers between six and eight. The 89 Zr–L4 complex showed similar stability to that of 89 Zr–DFO when incubated in either rat blood plasma or ethylenediaminetetraacetic acid challenge experiments. Positron imaging and biodistribution studies in mice showed that 89 Zr–L4 had similar pharmacokinetic behavior to that of 89 Zr–DFO, with rapid renal elimination and low residual activity in background tissues. A bifunctional version ofL4 (L5 ) was synthesized and conjugated to trastuzumab; an anti‐HER2/neu antibody. Immunopositron emission tomography imaging and biodistribution with 89 Zr–L5 –trastuzumab revealed high tumor to background ratios (tumor/blood ratio: 14.2±2.25) and a high tumor specificity that was comparable to the performance of 89 Zr–DFO–trastuzumab. Abstract : Targeting tumors : The preparation of four chelators and their 89 Zr complexes is described and their activity compared with the 89 Zr–desferrioxamine B complex. A bifunctional version of one chelator has also been synthesized and conjugated to the anti‐HER2/neu antibody trastuzumab for imaging in xenograft‐bearing mice (see figure).